Different counselors, many options: Career guidance and career plans in secondary schools - Fitzenberger, Bernd; Hillerich-Sigg, Anette; Sprietsma, Maresa (German Economic Review, 2020)
Career guidance assists students with the school-to-work transition. Based on a survey conducted in secondary schools in Germany, we analyze career guidance activities and how these affect career plans. The take-up of career guidance depends upon the school track attended, and the school and the class setting, while personal characteristics are barely relevant. The effects of counseling depend upon the type of counseling provider. Counseling by the employment agency reduces plans for educational upgrading and increases the probability of applying for an apprenticeship, while the effects of counseling by school counselors works in the opposite direction for lower track students.
Created from Fastlane, Scopus look-up
Keywords: Career guidance; Career planning; Counseling; Educational aspirations; School-to-work transition; Secondary school